ANALISIS BIAYA DIFERENSIAL DALAM RANGKA MENERIMA ATAU MENOLAK PESANAN KHUSUS PADA MEUBEL SABAR USAHA KABUPATEN MAJENE - Dahlia, Dahlia; Wahyuda, Nurul (Aksara Public, 2018)
This study aims to determine the application of differential costs in order to receive or reject a special order on the Meubel Sabar Usaha Majene Regarding the unemployment capacity contained in the company. The type of research method used is descriptive with quantitative approach, by taking samples from two special orders in 2016, which is 20 units kuseng windows and 10 pairs of school curriculum. Meanwhile, the type of data in this study is qualitative data and quantitative data, obtained from observations and interviews with owners and employees directly involved in the production process. The data analysis technique in this research is by identifying the cost behavior, then separating the cost of semi-variable by using the least squares method, the last calculate the differential earnings by taking into account the existing criteria.Based on the result of the research and discussion, concluded that the decision of Meubel Sabar Usaha to accept the two special orders is the right decision because the company get additional profit of Rp 1.179.473,00from the decision to accept the order 20 kuseng window, and 10 pairs of school fees, although special order prices are below the normal price set by the company.